An Assessment of Customer’s Preferences on The Selection of Takaful Over Conventional: A Case of Saudi Arabia - Faisal Nazir; Azman Bin Mohd. Noor (Institute for Research and Community Empowerment (LPPM TAZKIA), 2018)
This paper aims at assessing the motivational factors that influence the customer’s preferences of Takaful over conventional insurance. The customers’ information about the Takaful products and services based on sharia are identified in order to enable them differentiate Takaful and conventional insurance. The research uses mixed method of data collection. This comprises of questionnaires and in-depth interviews with the respondents from four selected Takaful industries in Saudi Arabia. The questionnaires were analysed using simple percentages and for the interviews, thematic analyses were used. Based on the findings of the study, the customer’s preferences on the selection of Takaful over conventional insurance include protection of Takaful product by sharia, support from the government. Similarly, the absence of risk incurred or transferred to participants, funds contributed in the spirit of brotherhood for all members. Moreover, another customer’s preferences is that contributions (tabarru’) are invested in non-interest based capitalization by the Takaful agents and profits are shared according to individual contributions. Based on Takaful, donations are established at the pooling system in line with sharia and they are formed on the bases of sympathy, consciousness of the idea of tabarru’ as well as abstaining from gharar, maysir and riba.